2020
DOI: 10.1021/acsami.0c18583
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Electrocatalytic Activity and Stability via Er0.4Bi1.6O3−δ In Situ Decorated La0.8Sr0.2MnO3−δ Oxygen Electrode in Reversible Solid Oxide Cell

Abstract: Weak electrocatalytic activity of the La 0.8 Sr 0.2 MnO 3−δ (LSM) oxygen electrode at medium and low temperatures leads to decreasing performance both in the solid oxide fuel cell (SOFC) mode and the solid oxide electrolysis cell (SOEC) mode. Herein, we design an Er 0.4 Bi 1.6 O 3−δ (ESB) functionalized La 0.8 Sr 0.2 MnO 3−δ (labeled as LSM/ESB) oxygen electrode via a one-step co-synthesis modified Pechini method. The unique LSM/ESB with polarization resistance of only 0.029 Ω•cm 2 at 750 °C enables a highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Four peaks are obtained, representing P 1 , P 2 , P 3 , and P 4 , respectively, corresponding to the low-frequency region (LF), medium-frequency region (IF), and high-frequency region (HF) . Based on the Adler–Lane–Steele model, the LF region corresponding to the P 1 peak reflects the gas diffusion process, the IF region corresponding to P 2 and P 3 peaks reflects the ion surface exchange process, and the HF region corresponding to the P 4 peak reflects the interface charge transfer process . It can be seen that different materials lead to different peaks in each region, and the place with the largest peak difference occurs in IF and HF regions, suggesting that the interface charge transfer process and ion surface exchange process are the main factors affecting the catalytic activity of the material.…”
Section: Resultsmentioning
confidence: 99%
“…Four peaks are obtained, representing P 1 , P 2 , P 3 , and P 4 , respectively, corresponding to the low-frequency region (LF), medium-frequency region (IF), and high-frequency region (HF) . Based on the Adler–Lane–Steele model, the LF region corresponding to the P 1 peak reflects the gas diffusion process, the IF region corresponding to P 2 and P 3 peaks reflects the ion surface exchange process, and the HF region corresponding to the P 4 peak reflects the interface charge transfer process . It can be seen that different materials lead to different peaks in each region, and the place with the largest peak difference occurs in IF and HF regions, suggesting that the interface charge transfer process and ion surface exchange process are the main factors affecting the catalytic activity of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The latter two can be collectively labeled as the adsorbed oxygen (O ads. ). , It is evident that the fraction of O ads. increases for both PBCFT-GDC and 6% PC/PBCFT-GDC anodes after a constant current density of 350 μA cm –2 is applied to the SOECs, due to the lattice oxygen spillover from TPBs onto the anode surface.…”
Section: Resultsmentioning
confidence: 99%
“…Through the distribution of relaxation time (DRT) analysis, the heterogeneous coherent interface between PrBaCo 2 O 5+d /Gd 0.1 Ce 1.9 O 2Àd composites prepared in a one-pot step was proven to enhance the oxygen exchange kinetics and boost the charge transfer subreaction. 88 Liu et al 89 compared the intrinsic properties and electrochemical performance of the one-pot co-synthesis LSM/ ESB with those of the mechanically mixed LSM-ESB electrode.…”
Section: Microstructural Tailoringmentioning
confidence: 99%
“…Through the distribution of relaxation time (DRT) analysis, the heterogeneous coherent interface between PrBaCo 2 O 5+ δ /Gd 0.1 Ce 1.9 O 2− δ composites prepared in a one-pot step was proven to enhance the oxygen exchange kinetics and boost the charge transfer sub-reaction. 88 Liu et al 89 compared the intrinsic properties and electrochemical performance of the one-pot co-synthesis LSM/ESB with those of the mechanically mixed LSM-ESB electrode. It showed that co-synthesized LSM/ESB electrode had a larger surface area (21.18 m 2 g −1 vs. 3.75 m 2 g −1 ), higher electronic conductivity (665 S cm −1 vs. 277 S cm −1 ), and tighter connection between LSM and ESB particles compared with the mechanically mixed LSM-ESB electrode, which resulted in the improved electrochemical performance (1.747 W cm −2 vs. 0.667 W cm −2 at 750 °C).…”
Section: Cathodementioning
confidence: 99%